Bodyweight Assessment of Enamelin Null Mice. (26th December 2012) - Chan, Albert H.-L.; Lertlam, Rangsiyakorn; Simmer, James P.; Wang, Chia-Ning; Hu, Jan C. C.
Abstract : The Enam null mice appear to be smaller than wild-type mice, which prompted the hypothesis that enamel defects negatively influence nutritional intake and bodyweight gain (BWG). We compared the BWG of Enam −/− and wild-type mice from birth (D0) to Day 42 (D42). Wild-type (WT) and Enam −/− (N) mice were given either hard chow (HC) or soft chow (SC). Four experimental groups were studied: WTHC, WTSC, NHC, and NSC. The mother's bodyweight (DBW) and the average litter bodyweight (ALBW) were obtained from D0 to D21. After D21, the pups were separated from the mother and provided the same type of food. Litter bodyweights were measured until D42. ALBW was compared at 7-day intervals using one-way ANOVA, while the influence of DBW on ALBW was analyzed by mixed-model analyses. The ALBW of Enam −/− mice maintained on hard chow (NHC) was significantly lower than the two WT groups at D21 and the differences persisted into young adulthood. The ALBW of Enam −/− mice maintained on soft chow (NSC) trended lower, but was not significantly different than that of the WT groups. We conclude that genotype, which affects enamel integrity, and food hardness influence bodyweight gain in postnatal and young adult mice.